Analysing Indoor Air Pollution: A Study on Pollutant Levels and Air Quality Assessment in Social Housing Properties - Vishnupriya Narayanan; Roshina Shaikh; Arman Hashemi; Heba Elsharkawy; Darryl Newport; Lucienne Basaly (Environmental Science and Sustainable Development, 2024)
Amid growing concerns over Indoor Air Quality (IAQ), this paper presents a comprehensive analysis of pollutants to assess the environmental health in a few Case Study Buildings (CSBs). The main objectives were to evaluate the levels of key Indoor Air Pollutants (IAPs) (PM10, PM2.5, CO, CO2, TVOCs) and relative humidity across multiple social housing properties and to analyze how occupant behaviormay affect IAQ. Utilizing quantitative measurements, the study investigates the range and exposure of the building occupants to IAPs. The methodology involves the systematic measurement of IAPs through the installation of data loggers, focusing on pollutant levels to evaluate air quality across multiple CSBs. Findings show fluctuation in pollutant levels, with some IAPs demonstrating consistently within the acceptable range while others exhibit sporadic spikes in pollutant concentrations. The results indicate that significant attention should be given to PM10, CO, and VOCs. This study underscores the importance of continuous monitoring and targeted interventions to mitigate poor IAQ and ensure healthier indoor environments for building occupants. Further research and implementation of effective measures are imperative to safeguard public health and well-being.